Evaluation of Somatostatin and CXCR4 Receptor Expression in a Large Set of Prostate Cancer Samples Using Tissue Microarrays and Well-Characterized Monoclonal Antibodies - Christoph Werner (Translational Oncology, 2020)
BACKGROUND: Prostate cancer (PCa) is the most common type of cancer among men in Western countries. Despite numerous therapeutic options, few treatments are available for patients with end-stage disease. In the present study, different somatostatin receptors (SSTs) and the chemokine receptor CXCR4 were evaluated for their suitability as novel therapeutic targets in PCa. MATERIALS AND METHODS: The expression of SST subtypes 1, 2A, 3, and 5 and of CXCR4 was evaluated in 276 PCa tumor samples on a tissue microarray (TMA) in 23 whole-block tumor samples and in 3 PCa cell lines by immunohistochemistry using well-characterized monoclonal antibodies. RESULTS: Overall, the frequency and intensity of expression of SSTs and CXCR4 were very low among the PCa samples investigated. Specifically, SST5, SST2A, and SST3 were expressed, albeit at low intensity, in 10.5%, 9.1%, and 0.7% of the TMA samples, respectively. None of the TMA samples showed SST1 or CXCR4 expression. Only a single small-cell-type neuroendocrine carcinoma that was coincidentally included among the whole-block samples exhibited strong SST2A, SST5, and CXCR4 and moderate SST3 expression. Independent of the tumor cells, the tumor capillaries in many of the PCa samples were strongly positive for SST2A, SST3, SST5, or CXCR4 expression. SST expression in the tumor cells was associated with advanced tumor grade and stage. CONCLUSION: Overall, SST and CXCR4 expression levels are clearly of no therapeutic relevance in PCa. SST- or CXCR4-based therapy might be feasible, however, in rare cases of small-cell-type neuroendocrine carcinoma of the prostate.